Removal of heavy metals from single species and composite species aqueous solutions using coco peat as sorbent material - Ong, Dennis C.
Coco peat has been found to have good sorption potential, and the applicability of this agricultural waste in removing single heavy metal species from aqueous solutions has been investigated. However, since actual wastewaters commonly contain more than one heavy metal species, competitive interactions between heavy metal species will most likely occur. As such, this study is conducted to assess the applicability of coco peat for treatment of wastewater containing more than one heavy metal species. For this purpose, the physico-chemical properties of the coco peat that may contribute to or affect its sorption capacity were determined. Column leaching tests were conducted on laboratory-prepared aqueous solutions containing Pb2+, Cu2+ and Fe3+, as well as a tractor compound, to evaluate the behavior of nonreactive and reactive solutes through the coco peat bed. Mechanism involved in the heavy metal removal were determined by desorption tests, pH profiles, and FTIR analysis. Results showed that values of the physico-chemical properties of coco peat indicated the material's high potential for sorption of heavy metals from wastewater. The resulting selectivity sequence for the three heavy metals was Pb2+>Cu2+>Fe3+, indicating high preference of coco peat for sorption of the environmentally regulated Pb2+, as revealed by its high partition coefficient values obtained from both single species and composite species leaching tests. The pH profiles and desorption results suggest the occurrence of ion exchange, chemisorption and precipitation mechanisms. FTIR analyses reveal the possible involvement of certain functional groups in the removal of heavy metals from the aqueous solutions by coco peat.